EVALUASI PENGGUNAAN MODUL ILUSTRASI BAGIAN-BAGIAN BUSANA DALAM MENDUKUNG PROSES PEMBELAJARAN DESAIN MODE - Nasta Irena Savela; Arrsy, Esty Nurbaity; Prabawati, Melly (LPPM, Universitas Negeri Jakarta, 2024)
This study aims to evaluate the quality of teaching materials in the form of a fashion illustration module, specifically focusing on collar and sleeve materials, designed to support students' independent learning in the Fashion Drawing course within the Fashion Design Education Study Program. The module was developed in accordance with the principles of vocational learning, which emphasize the integration of theory and practice, as well as the characteristics of modern learning modules. The research method employed a quantitative approach, utilizing a pre-experimental one-shot case study design and quantitative descriptive data analysis. The assessment was conducted by four expert panelists using an assessment scale instrument that encompassed aspects of the teaching materials (material, presentation, and language) and module characteristics (self-instructional, self-contained, stand-alone, adaptive, and user-friendly). The results showed that the module was in the